THE EFFECTIVENESS OF E-BOOKLET COORDINATION SYSTEM ON LEARNING OUTCOMES OF PHASE F STUDENTS AT SMAN 13 PADANG: EFEKTIVITAS E-BOOKLET SISTEM KOORDINASI TERHADAP HASIL BELAJAR PESERTA DIDIK FASE F DI SMAN 13 PADANG - Avichena, Avichena; Umarella , Melati. I.S (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
The development of learning tools is an integral part of innovation in education. Learning tools are designed to enhance the learning experience, facilitate understanding of complex concepts, and promote active engagement in a variety of learning processes. Learning tools that are often developed by students are learning resources. E-booklets are a learning resource that is quite promising, considering the complexity of the material that must be delivered and the need to keep up with technological developments which are very important. Even so, research on the effectiveness of using e-booklet coordination systems on student learning outcomes is still limited. Facing these dynamics, strong empirical evidence is needed about the effectiveness of using e-booklets in improving student learning outcomes. This research aims to fill the knowledge gap by evaluating in detail the extent of the effectiveness of using e-booklet coordination systems on student learning outcomes. This type of research is quasi-experimental with a Posttest-only control group design research design using purposive sampling techniques. The learning outcomes of the group that received treatment using the e-booklet coordination system in learning activities were higher than the group without treatment using the e-booklet coordination system. Based on field facts and various existing considerations, it can be said that learning using e-booklets is more effective for learning outcomes when compared to without using e-booklets. It can be concluded that the difference in treatment between the experimental class and the control class had a very significant effect.